The mental health of farmers - Gregoire, A. (Occupational medicine (Oxford), 2002)
Farmers are subject to a number of unique occupational stressors, many of which have been aggravated in recent years by changes in farming practice and by economic factors. These are probably part of the explanation for the high rates of suicide in farmers and farm workers, which in the UK account for the largest number of suicides in any occupational group. Suicide is usually associated with mental illness, which, in farming communities, appears to be particularly stigmatized and poorly understood. This affects health‐seeking behaviour, which is compounded by the geographical isolation and inaccessibility of many services in rural areas. Our current understanding of these issues suggests a number of potentially valuable interventions.